Penggunaan Ragi Komersial pada Pengolahan Etanol dari Nira Aren - A. LAY (Buletin Palma, 2009)
Use of Commercial Yeasts on Etanol Processing from Palm NeeraThe objective of this research was to find out commercial yeasts which effective for fermentation sugar palm neera become etanol, efficient processing technique and it can be operated by the farmers/the farmer groups. The research was done from March to June 2009, in the Laboratory of Indonesia Coconut and Other Palmae Research Intitute. The research was conducted in factorial experiment 5 x 4 x 2, using completed randomized design. Factor A is commercial yeast, which consists of A1 = Fermipan, A2 = Mauri-pan, A3 = Gold-Pakmaya, A4 = BrewMax, and A5 = Without yeast. (Fermipan, Mauri-pan, Gold-Pakmaya, BrewMax and without yeast. Factor B is fermentation period which consists of B1 = 0 day, B2 = 2 days and B3 = 3 days. Ethanol processing was conducted by using fermentation and distillation process. The result showed that the suitable yeast for fermentation were Gold-Pakmaya and Fermipan yeast. Using a single destillator, laboratory scale, the first and second processes, produced etanol 28-43% and 72-77%, respectively. Processing etanol 30-32% and 72-77% is economically feasible.